Supervised Nasal Saline Irrigations in Otitis-Prone Children - Torretta, Sara; Pignataro, Lorenzo; Ibba, Tullio; Folino, Francesco; Fattizzo, Miriam; Marchisio, Paola (Frontiers in Pediatrics, 2019)
Objectives: To retrospectively investigate the impact of supervised daily nasal saline irrigations (NSI) with 0.9% saline solution in children with a history of recurrent acute otitis media (RAOM). Methods: A retrospective pilot study was planned to evaluate the possible effect of supervised NSI in reducing the number of acute otitis media (AOM) episodes in otitis-prone children aged 1-5 years, compared to children not instructed to correct NSI performance. Results: Analysis was based on the data contained in 173 charts (57.3% males, mean age of 30.9 ± 7.3 months). 52.0% of children had not been instructed to perform NSI, while the remaining (48.0%) patients had received supervised NSI. At the four-months follow-up visit a significant reduced number of AOM episodes (1.03 ± 0.14 vs. 2.08 ± 0.16; p-value< 0.001) as well as antibiotic treatments (1.48 ± 0.17 vs. 2.59 ± 0.18; p-value< 0.001) was documented in children receiving supervised NSI compared to those not instructed for NSI performance. Conclusions: These data suggest that NSI should be considered in the therapeutic management of children with RAOM, and should be routinely prescribed as a daily adjunctive treatment to reduce acute infectious exacerbations in otitis-prone patients. Accurate parents training is crucial in order to improve children compliance and treatment effectiveness.